2014
DOI: 10.1007/s00066-014-0778-y
|View full text |Cite
|
Sign up to set email alerts
|

Förderung der integrinbasierten Meningeomzellmigration durch Bestrahlung mit Photonen, nicht jedoch durch Bestrahlung mit Kohlenstoffionen

Abstract: Photon but not carbon-ion IR promotes serum-based meningioma cell migration. Fibronectin receptor integrin ανβ1 signaling can be identified as an important mechanism for serum- and photon-induced migration of WHO class I meningioma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Madani et al describe that dose-painting intensity-modulated proton therapy (IMPT) using a SIB is a feasible therapy option with excellent dose coverage with minimal or no dose to brain, brainstem or optical system [ 38 ]. A study by Simon concludes that carbon-ion RT could be the preferred therapy option [ 39 ]. Similarly, Harrabi et al describe that proton beam RT shows dosimetric advantages over conventional radiotherapy that might be essential for neurologic function [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Madani et al describe that dose-painting intensity-modulated proton therapy (IMPT) using a SIB is a feasible therapy option with excellent dose coverage with minimal or no dose to brain, brainstem or optical system [ 38 ]. A study by Simon concludes that carbon-ion RT could be the preferred therapy option [ 39 ]. Similarly, Harrabi et al describe that proton beam RT shows dosimetric advantages over conventional radiotherapy that might be essential for neurologic function [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are two recent reports confirming our observation on charged particle effects on cell migration and related signaling pathways. Simon et al ( 44 ) were able to show that migration of meningioma cells was promoted by photon but not by carbon ion irradiation. Our results on an increased cell migration associated with an elevated phosphorylation status of the EGFR and AKT–ERK1/2 pathway following X-ray but not carbon irradiation was partially confirmed by corresponding findings of Jin and colleagues ( 45 ).…”
Section: Discussion and Resumementioning
confidence: 99%
“…In meningioma, it has been demonstrated that integrins are widely expressed in a subtype and grading-dependent manner [46]. The integrins αvβ1, αvβ3, αvβ5 have been directly implicated in invasion [47][48][49][50]. Integrins seem to provide a reasonable target for specific anti-invasive therapy in meningioma, with two studies reporting promising results using preclinical orthotopic mouse meningioma models [50,51].…”
Section: Cell-cell and Cell-extracellular Matrix Interactionsmentioning
confidence: 99%